Declarations of Dependence : The Long Reconstruction of Popular Politics in the South, 1861-1908 - Downs, Gregory P. (Book collections on Project MUSE., 2011)
Through an examination of the pleas and petitions of ordinary North Carolinians, Downs contends that the Civil War redirected, not destroyed, claims of dependence by exposing North Carolinians to the expansive but unsystematic power of Union and Confederate governments, and by loosening the legal ties that bound them to husbands, fathers, and masters.